The altruistic rich? Inequality and other-regarding preferences for redistribution - Dimick, M; Rueda, D; Stegmueller, D (Now Publishers, 2017)
What determines support among individuals for redistributive policies? Do individuals care about others when they assess the consequences of redistribution? This paper proposes a model of other-regarding preferences for redistribution, which we term income-dependent altruism. Our model predicts that an individual’s preferred level of redistribution is decreasing in income, increasing in inequality, and, more importantly, that the inequality effect is increasing in income. Thus, even though the rich prefer less redistribution than the poor, the rich are more responsive, in a positive way, to changes in inequality than are the poor. We contrast these results with several other prominent alternatives of other-regarding behavior. Using data for the US from 1978 to 2010, we find significant support for our claims.